Evaluation of the effectiveness of the Internet as an information source as perceived by research professionals of Andersen consulting - Nuyda, Anya Alexandra G.
This study focused on the evaluation of the Internet as an information source as perceived by research professionals of Andersen Consulting. It also identified the problems encountered by these research professionals when searching. A survey was conducted to generate the data and was carried out for a period of 2 weeks.